2019
DOI: 10.1111/ffe.13075
|View full text |Cite
|
Sign up to set email alerts
|

New method for determining PSN curves in terms of equivalent fatigue lives

Abstract: A new method for determining the P‐S‐N curves is proposed by the probabilistic analysis of the mixed samples that are composed of the testing fatigue lives and equivalent fatigue lives. The equivalent fatigue lives at each level are converted from all the testing data at all the testing levels according to the equivalent fatigue failure probability, where the life distributions are determined by the medians of logarithmic fatigue lives at respective levels and a unified coefficient of variation. Comparison res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Besides, Xie et al 17 proposed a backward statistical inference method and accurately estimated the life distribution of small samples and the P-S-N equation based on the mechanism called the consistency of sample percentiles and the linear relationship between life standard deviation and stress. Bai et al 18 and Li et al 19 improved this method respectively. And Liu and Pan et al 20,21 applied the bootstrap method to expand the fatigue data under the highest load level into large samples and applied the backward statistical inference method to curve fitting.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Xie et al 17 proposed a backward statistical inference method and accurately estimated the life distribution of small samples and the P-S-N equation based on the mechanism called the consistency of sample percentiles and the linear relationship between life standard deviation and stress. Bai et al 18 and Li et al 19 improved this method respectively. And Liu and Pan et al 20,21 applied the bootstrap method to expand the fatigue data under the highest load level into large samples and applied the backward statistical inference method to curve fitting.…”
Section: Introductionmentioning
confidence: 99%
“…Another noteworthy article which provides a critical review of the P-S-N approach is [32]. Several other authors have indicated the significance of the P-S-N approach as a means of evaluating this relationship [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, each P-S-N curve is fitted with one of methods listed above or a combination of these methods 9,[11][12][13] .According to sampling theory, the larger the sample, the higher the accuracy of the tests conducted on the sample. However, owing to high costs and long fatigue testing times, it is difficult to achieve sample sizes that satisfy sampling theory requirements, especially in the case of large-sized structural parts or expensive parts [14][15][16] . The maximum likelihood method can fit the P-S-N curve with a small sample 17,18 , but the life means and standard deviations under each stress level must have been measured with high accuracy to achieve good results.…”
mentioning
confidence: 99%